L’augmentation de contenu venant des relations publiques dans les nouvelles québécoises entre 1988 et 2016 : le cas de six quotidiens - Chantal Francœur (Communiquer)
Over the last thirty years the amount of PR content in Québécois news stories has increased. This trend is the key finding to emerge from a quantitative analysis of six Quebec dailies that we undertook in 2016, and that echoes the methodological approach used by Tremblay, Saint-Laurent, Saint-Jean and Carontini (1988) in their earlier study of the same phenomenon. Whereas Tremblay et al. established that in 1988, almost 50% of Quebec news stories contained content derived from a PR source, our study found that by 2016, that figure had risen to between 66 and 76%. This means that at least two thirds, and as much as three quarters, of news stories in Quebec today contain information and/or references provided to the journalist by a PR professional.